Genome-wide interaction analysis identified low-frequency variants with sex disparity in lung cancer risk. Issue 16 (9th February 2022) - Li, Yafang; Xiao, Xiangjun; Li, Jianrong; Byun, Jinyoung; Cheng, Chao; Bossé, Yohan; McKay, James; Albanes, Demetrios; Lam, Stephen; Tardon, Adonina; Chen, Chu; Bojesen, Stig E; et al.
Abstract: Differences by sex in lung cancer incidence and mortality have been reported which cannot be fully explained by sex differences in smoking behavior, implying existence of genetic and molecular basis for sex disparity in lung cancer development. However, the information about sex dimorphism in lung cancer risk is quite limited despite the great success in lung cancer association studies. By adopting a stringent two-stage analysis strategy, we performed a genome-wide gene–sex interaction analysis using genotypes from a lung cancer cohort including ~ 47 000 individuals with European ancestry. Three low-frequency variants (minor allele frequency < 0.05), rs17662871 [odds ratio (OR) = 0.71, P  = 4.29×10 −8 ); rs79942605 (OR = 2.17, P  = 2.81×10 −8 ) and rs208908 (OR = 0.70, P  = 4.54×10 −8 ) were identified with different risk effect of lung cancer between men and women. Further expression quantitative trait loci and functional annotation analysis suggested rs208908 affects lung cancer risk through differential regulation of Coxsackie virus and adenovirus receptor gene expression in lung tissues between men and women. Our study is one of the first studies to provide novel insights about the genetic and molecular basis for sex disparity in lung cancer development.